Private pensions for the self-employed: Challenges and options for reform - Jonathan Cribb; Carl Emmerson; Laurence O'Brien; David Sturrock (Institute for Fiscal Studies (IFS), 2024)
There have been widespread concerns about the patterns of retirement saving amongst self-employed workers, who now make up just over one in eight of the whole labour force. Most strikingly, the fraction of self-employed workers earning over 10,000 who are making contributions to a private pension has been around 20% since the early 2010s. That compares with over 80% among employees. Self-employed workers who want to save in a pension must arrange their own personal pension, in contrast to most employees who will be automatically enrolled into a workplace pension by their employer. However, many self-employed workers have private pensions from previous employment, save in other forms of wealth, or are married to or cohabiting with someone who does have a workplace pension. The state pension system has also become more generous for the self-employed since the introduction of the new state pension in 2016. This report summarises the patterns of saving and wealth among the self-employed, including new modelling on the potential adequacy of saving for the self-employed compared with standard benchmarks. From the concerning trends we uncover, it is clear that reform is overdue; we therefore also set out some policy options for policymakers to choose between.
Keywords: 330; Savings; pensions and wealth; Private pensions; Retirement; Savings; Wealth